Criopreservação de sêmen de tambaqui Colossoma macropomum em criotubo - Carvalho, Allan Charles Marques de (2013)
The semen cryopreservation in cryotubes reduces the time needed for filling, freezing and thawing of the samples, while optimizing the procedures for artificial fertilization. However, no study has yet been performed with tambaqui semen in this container. The aim of this study was to evaluate the influence of cryotubes (1.6 and 4.5 mL) and thawing time (60ºC/70s and 60ºC/90 s) on the quality and fertility of tambaqui cryopreserved semen. For that, semen samples were diluted in freezing solution (1:9) composed with 75% glucose 290 mOsm , 10% methylglycol and 5% egg yolk, and frozen in liquid nitrogen vapor (in a dry shipper), and stored in liquid nitrogen (-196 °C). The semen samples was thawed at 60ºC in bath water during 70s or 90s and the semen quality was evaluated (Total motility - MT; Progressive motility - MP; Curvilinear velocity - VCL; Straight-line velocity - VSL and Average path velocity - VAP). In this study was also determined the time viability of spermatozoa thawed, maintained under refrigeration at 5°C, and assessed over 24 hours. Besides the kinetic parameters were evaluated sperm morphology and membrane integrity of spermatozoa. The fertilizing capacity of semen was evaluated from the samples thawed in the best time. All parameters of sperm kinetic showed higher values when the semen samples were thawed in 90 s compared to 70 s, independently of cryotube type. No significant differences were observed in sperm kinetic parameters after thawing between samples frozen in 1.6 ml and 4.5 mL cryotubes, except for total motility that was higher in 1.6 mL (47 ± 14% ) compared with 4.5 mL cryotubes (40 ± 11%), independently of thawing time. After activation, the spermatozoa significantly reduced the values of kinetic parameters within 37 seconds, except the MT which remained constant during this period. Relying on the sperm parameters evaluated (VCL, VSL, VAP and membrane integrity for both cryotubes and MT, MP and morphology only for 1.6 mL cryotube) the frozen semen maintained the quality during 3h after thawing. The fertilization rate obtained with fresh semen (74±6%) was higher than cryopreserved semen (1.6 mL - 45±9% and 4.5 mL - 41±12%). The two cryotubes did not differ in this parameter. A high correlation (p <0.05) was observed between fertility and sperm kinetics parameters (MT - 89%, MP - 86%; VCL - 79%; VSL - APV and 69% - 78%). It is concluded that 1.6 and 4.5 mL cryotubes can be used in the cryopreservation of tambaqui semen being recommended to be thawed at 60°C for 90s and their use in fertilization procedures within 3 hours after thawing since kept at 5°C.